2012
DOI: 10.36834/cmej.36569
|View full text |Cite
|
Sign up to set email alerts
|

Improving Family Medicine Residents’ Written Communication

Abstract: Background: Although competency in written communication is a core skill, written communication is seldom the focus of formal instruction in medical education. The objective of this intervention was to implement a selfassessment strategy to assist learners in improving their letter writing skills and then to evaluate its feasibility, reliability and potential educational value.Methods: Eight first-year family medicine residents from two teaching sites completing a six month family medicine rotation used a self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…A pesquisa mostra que os médicos da atenção primária da RAS estudada, na grande maioria das vezes, referenciam seus pacientes com informações de dados demográficos e queixa principal ou motivo da referência. Esses dados expõem o contraste com o estudo desenvolvido no Canadá por François, 11 em que os residentes em Medicina da Família auditaram suas próprias cartas de encaminhamento, e a única variável que não estava presente em 70% dos encaminhamentos, entre aquelas que este trabalho também analisou, era a informação sobre alergias. Essa diferença pode ser justificada pelo fato de os médicos da RAS estudada verem o encaminhamento como um processo necessário para o paciente ser referenciado a um especialista, e não como um meio de comunicação para troca de informações, como os residentes de Medicina da Família canadenses.…”
Section: Discussionunclassified
“…A pesquisa mostra que os médicos da atenção primária da RAS estudada, na grande maioria das vezes, referenciam seus pacientes com informações de dados demográficos e queixa principal ou motivo da referência. Esses dados expõem o contraste com o estudo desenvolvido no Canadá por François, 11 em que os residentes em Medicina da Família auditaram suas próprias cartas de encaminhamento, e a única variável que não estava presente em 70% dos encaminhamentos, entre aquelas que este trabalho também analisou, era a informação sobre alergias. Essa diferença pode ser justificada pelo fato de os médicos da RAS estudada verem o encaminhamento como um processo necessário para o paciente ser referenciado a um especialista, e não como um meio de comunicação para troca de informações, como os residentes de Medicina da Família canadenses.…”
Section: Discussionunclassified
“…What evidence there is suggests, unsurprisingly, that clinic letter writing is not an innate skill and improves with education. 5,6 What makes a 'good' clinic letter is a topic for debate. Several studies from various specialities have looked at the differing opinions of GPs and patients regarding letter quality.…”
Section: Clinic Letter Writing Is a Skill And Is Often Poorly Performmentioning
confidence: 99%
“…7 The participants were encouraged to seek feedback from colleagues, GPs and patients about their letter writing; feedback has been shown to both improve letter quality and be welcomed by trainees. 3,5,7 By the end of the session the participants had considered the letters from three different perspectives and derived by consensus the important features of an effective letter. All groups concluded that they would like to produce three letters.…”
Section: -45 Mins Summing Upmentioning
confidence: 99%
See 2 more Smart Citations